1982
DOI: 10.1177/073168448200100407
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Properties of Portland Cement Reinforced with Kevlar Fibers

Abstract: Composite specimens for tensile testing were made from various amounts of Kevlar fibers in Portland cement. Testing revealed about 50% improvement in the Elastic Modulus and yield strength over the unreinforced cement. The maximum amount of fibers, which was possible to add without destroying the continuity of the cement matrix, was about 2%. Specimens containing less than about 0.15% of fibers failed in a brittle manner like a single phase material. Specimens containing more than that amount of fibers display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The vesicular shape and size of the polymer imparts beneficial mechanical properties to cement through cement reinforcement, as well as, elasticity. [11,13,22] Polyamide reinforcement and strengthening are required because ordinary Portland cement lacks tensile strength to withstand extreme forces from any thermomechanical stress. In this study, reinforcement is provided by the embedment of polyaramid vesicles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The vesicular shape and size of the polymer imparts beneficial mechanical properties to cement through cement reinforcement, as well as, elasticity. [11,13,22] Polyamide reinforcement and strengthening are required because ordinary Portland cement lacks tensile strength to withstand extreme forces from any thermomechanical stress. In this study, reinforcement is provided by the embedment of polyaramid vesicles.…”
Section: Resultsmentioning
confidence: 99%
“…[7,8] Interest in cement-polymer composites and cements with embedded polymer powder/fibers have also contributed to some important chemical research and development. [6,[9][10][11][12] However, cementing in subterranean zones with higher temperature and pressures requires innovation in chemical additives to overcome cement integrity challenges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, under high rate loading, the specimens prepared with fibers having 24 mm length exhibited higher strain energies than those prepared with 12 mm fibers. Konczalski and Piekarski [18] investigated the influence of Kevlar fibers on the tensile properties of ordinary Portland cement and found that using Kevlar significantly improves the elastic modulus and fracture energy.…”
Section: Introductionmentioning
confidence: 99%